2022
DOI: 10.1111/ajco.13730
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of immune checkpoint receptor expression in patients with lymphoma: Association with disease status and clinical outcomes

Abstract: Introduction Little is known about the expression of immune checkpoint receptors in the peripheral blood of lymphoma patients. Herein, we assessed the expression of inhibitory checkpoint receptors, including CTLA‐4, PD‐1/PDL‐1, LAG‐3, and TIM‐3 in the peripheral blood of lymphoma patients and its correlation with the clinical outcomes of patients. Therefore, 47 classical Hodgkin lymphoma (cHL), 48 non‐Hodgkin lymphoma patients with diffuse large B‐cell lymphoma (DLBCL) subtype, and 30 healthy controls were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…After detecting the expression of PD-1 and LAG-3 in DLBCL tissues in 174 patients,we found that PD-1 and LAG-3 were widely expressed in TILs (Figure 1) and were correlated with bone marrow involvement.The expression of LAG-3 was also different at high and low LDH levels (Table 1). Studies have indicated that the expression level of LAG-3 in relapsed DLBCL patients is up-regulated compared with that of newly diagnosed DLBCL patients, and it is related to PS score (23), suggesting that…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After detecting the expression of PD-1 and LAG-3 in DLBCL tissues in 174 patients,we found that PD-1 and LAG-3 were widely expressed in TILs (Figure 1) and were correlated with bone marrow involvement.The expression of LAG-3 was also different at high and low LDH levels (Table 1). Studies have indicated that the expression level of LAG-3 in relapsed DLBCL patients is up-regulated compared with that of newly diagnosed DLBCL patients, and it is related to PS score (23), suggesting that…”
Section: Discussionmentioning
confidence: 99%
“…After detecting the expression of PD-1 and LAG-3 in DLBCL tissues in 174 patients,we found that PD-1 and LAG-3 were widely expressed in TILs ( Figure 1 ) and were correlated with bone marrow involvement.The expression of LAG-3 was also different at high and low LDH levels ( Table 1 ). Studies have indicated that the expression level of LAG-3 in relapsed DLBCL patients is up-regulated compared with that of newly diagnosed DLBCL patients, and it is related to PS score ( 23 ), suggesting that the high expression of PD-1 and LAG-3 immune checkpoints may be related to the aggressiveness of DLBCL.In addition, we found a correlation between the expression level of PD-1 and LAG-3 protein ( Table 4 ), indicating that there are some cascades between PD-1 and LAG-3 in the co-inhibitory receptor pathway, which jointly maintain immune microenvironment homeostasis.At the same time, under the long-term stimulation of tumor cells, PD-1+LAG-3+T cells further exhaust, and their ability to produce cytokines and cytotoxic particles is greatly reduced ( 24 ). Most importantly, we found that high expression of LAG-3 in TILs was associated with lower survival in DLBCL patients ( Figures 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 is a chemokine secreted by osteoclasts, endothelial cells, and epithelial cells of the central nervous system, and is a pro-inflammatory mediator secreted by cancer-related fibroblasts. CXCL12 regulates neoangiogenesis, tumor cell proliferation, and migration of various solid tumors by binding to chemokine 4 (CXCL4)[ 15 ]. Blocking the CXCL12/CXCL4 pathway can enhance tumor T-cell infiltration, reduce regulatory T-cell production, and enhance antitumor activity[ 16 ].…”
Section: Discussionmentioning
confidence: 99%